2015
DOI: 10.1186/s12610-015-0018-z
|View full text |Cite
|
Sign up to set email alerts
|

Possible germ cell-Sertoli cell interactions are critical for establishing appropriate expression levels for the Sertoli cell-specific MicroRNA, miR-202-5p, in human testis

Abstract: BackgroundTo examine human microRNA expression in fertile men and subsequently to compare expression patterns of miRNAs in fertile and infertile men, specifically men with Sertoli Cell Only (SCO) histopathology.MethodsTesticular tissues from men with azoospermia and SCO, as well as those of men with normal spermatogenesis, were analyzed. MicroRNA was isolated using the miRCURY™ RNA Purification Kit. A miRCURY LNA™ Universal RT system was used for detection of microRNA by quantitative real-time PCR. MicroRNA lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 25 publications
5
48
0
Order By: Relevance
“…Seven miRNAs that were significantly decreased in NOA patients but markedly increased in asthenozoospermia patients were found to be miR-34c-5p, miR-122, miR-146b-5p, miR-181a, miR-374b, miR-509-5p, and miR-513a-5p (Table 2). Although testicular tissues of the patients were not analyzed in this study, miR34c-5p, miR-122, miR-181a, and miR-509-5p have also been shown to be decreased in testicular tissues of NOA patients in several different studies, confirming the utility of these miRNAs as noninvasive diagnostic tools for NOA [99,107,108,110]. Interestingly, in patients with asthenozoospermia, miR-122 has later been reported to be downregulated in spermatozoa samples [105], by contrast with its abovementioned upregulation observed in seminal plasmas [102].…”
Section: Seminal Fluidal Mirnas and Male Infertilitymentioning
confidence: 94%
See 2 more Smart Citations
“…Seven miRNAs that were significantly decreased in NOA patients but markedly increased in asthenozoospermia patients were found to be miR-34c-5p, miR-122, miR-146b-5p, miR-181a, miR-374b, miR-509-5p, and miR-513a-5p (Table 2). Although testicular tissues of the patients were not analyzed in this study, miR34c-5p, miR-122, miR-181a, and miR-509-5p have also been shown to be decreased in testicular tissues of NOA patients in several different studies, confirming the utility of these miRNAs as noninvasive diagnostic tools for NOA [99,107,108,110]. Interestingly, in patients with asthenozoospermia, miR-122 has later been reported to be downregulated in spermatozoa samples [105], by contrast with its abovementioned upregulation observed in seminal plasmas [102].…”
Section: Seminal Fluidal Mirnas and Male Infertilitymentioning
confidence: 94%
“…In a more recent study conducted with testicular tissue samples from five azoospermic men with SCO syndrome, miRNAs with the highest fold reductions in comparison to controls were found to be miR-34c-5p, miR-126, miR-191, miR-10b, and miR-202-5p [110]. Further experimentation with immunohistochemistry showed a specific localization of miR-202-5p to Sertoli cells of normal fertile men, but not in those of infertile men with SCO.…”
Section: Seminal Plasmamentioning
confidence: 99%
See 1 more Smart Citation
“…The number and state of the germ cells in the gonads is the major determinant of the level of AMH in the circulation. This is most clearly established for females (Visser et al 2012), but it may also be the case for males, as germ cells regulate Sertoli cells (O'Shaughnessy et al 2008, Cool et al 2012, Dabaja et al 2015. Consequently, AMH is uniquely and ideally placed to convey information about the current and future reproductive capacity of an individual.…”
Section: Circulatory Amh May Signal Reproductive Status In Adultsmentioning
confidence: 99%
“…For example, miR‐34b and miR‐34c regulate the differential expression of AQN‐1 protein ( AQN‐1 ), hyaluronan synthase 3 ( HAS3 ), ring finger protein 4 ( RNF4 ), sperm mitochondria‐associated cysteine‐rich protein ( SMCP ), and sperm adhesion molecule 1 ( SPAM1 ) between mature and immature porcine testes (Luo et al, ), indicating that these miRNAs play important roles in species‐ and stage‐specific male germ cell development. Similarly, the testicular somatic cells of fertile and infertile males express miRNAs differentially, for example miR‐202‐5p, a member of the let‐7 family, is selectively expressed in Sertoli cells of fertile males with normal germ cells, but not in the Sertoli cells of infertile males (Dabaja et al, ). Previous studies also showed that miR‐202‐5p, which is a downstream mediator of the testis‐determining factor SOX9 (Wainwright et al, ), is expressed in Sertoli cells in the early XY gonad (Rakoczy et al, ) and its expression is up‐regulated again in the testis at later developmental stages (Ro et al, ).…”
Section: Roles Of Mirna In Male Reproductionmentioning
confidence: 99%